2020
DOI: 10.1021/acssensors.0c00908
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Gold Nanostar-Enhanced Multimodal Photoacoustic Microscopy and Optical Coherence Tomography Molecular Imaging To Evaluate Choroidal Neovascularization

Abstract: Although photoacoustic microscopy (PAM) and optical coherence tomography (OCT) allow visualization of the retinal microvasculature, distinguishing early neovascularization from adjacent vessels remains challenging. Herein, gold nanostars (GNSs) functionalized with an RGD peptide were utilized as multimodality contrast agents for both PAM and OCT. GNSs have great absorption and scattering characteristics in the near-infrared region where most vasculature and tissue generates a less intrinsic photoacoustic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
(86 reference statements)
1
36
0
Order By: Relevance
“…The earlier research group recently demonstrated that gold nanoprisms with strong scattering in the NIR‐II window could be used as the contrast agents for deep‐tissue OCT. After intravenous injection of PEGylated gold nanoprisms, significant improvement of the contrast in OCT angiograms was achieved, allowing for in vivo melanoma tumor detection based on the tumor microvasculature characterization. [ 39 ] In another recent study from Nguyen et al, gold nanostars functionalized with an RGD peptide were utilized as the contrast agents to evaluate choroidal neovascularization in living rabbits by multimodal PA microscopy and OCT. [ 40 ] As shown in Figure 4b, the peak PA amplitudes were obtained at wavelength matching with the absorption of gold nanostars, where PA contrast increased by up to 17‐folds and OCT intensities increased 167%.…”
Section: Gold Nanomaterials For Optical Detection and Single‐mode Imagingmentioning
confidence: 95%
“…The earlier research group recently demonstrated that gold nanoprisms with strong scattering in the NIR‐II window could be used as the contrast agents for deep‐tissue OCT. After intravenous injection of PEGylated gold nanoprisms, significant improvement of the contrast in OCT angiograms was achieved, allowing for in vivo melanoma tumor detection based on the tumor microvasculature characterization. [ 39 ] In another recent study from Nguyen et al, gold nanostars functionalized with an RGD peptide were utilized as the contrast agents to evaluate choroidal neovascularization in living rabbits by multimodal PA microscopy and OCT. [ 40 ] As shown in Figure 4b, the peak PA amplitudes were obtained at wavelength matching with the absorption of gold nanostars, where PA contrast increased by up to 17‐folds and OCT intensities increased 167%.…”
Section: Gold Nanomaterials For Optical Detection and Single‐mode Imagingmentioning
confidence: 95%
“…Among these piezoelectric transducers, needle transducers are most commonly used. So far, OC-PAM using needle transducers has been applied in choroidal and retinal imaging [119][120][121][122][123][124][125][126][127] extensively. Some technical advancements of needle-transducer-based OC-PAM systems have also been reported such as for dynamic focusing 128,129 and for incorporating additional imaging modalities.…”
Section: System Configurations For Dual Modality Oct-paimentioning
confidence: 99%
“…Particularly, based on the much stronger and tighter optical beam than the acoustic beam, OR-PAM takes extreme advantage of the high resolution over AR-PAM. In addition, with the rich optical absorption contrast, OR-PAM becomes a promising imaging tool in many research fields including biology, dermatology, neurology, oncology, ophthalmology, and pathology [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ]. Typical OR-PAM systems implement a confocal and coaxial structure of the excitation light beam and the PA emission beam to maximize the signal-to-noise ratio (SNR) and optimize the spatial resolutions [ 6 , 8 , 12 , 17 ].…”
Section: Introductionmentioning
confidence: 99%